Artículos científicos: Preparación, diseño y publicación - Serna, Giovanna; Gutiérrez, Giovanna; Zenozain, Carmen; Damián, Roberto; Yanowsky, Guillermo; Vargas-Portugal, Kevin (2023)
Scientific articles are an essential tool in the world of research and science. They are a way for researchers to share their findings with the scientific community and the general public. In addition, they are an important source of information and knowledge in different fields of study. This book will discuss the challenges associated with writing scientific articles and how to overcome them to achieve success in the world of research. Tips and resources will also be provided to help researchers improve their science writing skills.
Keywords: scientific article; scientific research; research methodology; academic publications